2013
DOI: 10.1177/0218492313499352
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative levosimendan in ischemic mitral valve repair

Abstract: Preoperative treatment with levosimendan in patients undergoing coronary artery bypass grafting and mitral valve repair resulted in improved hemodynamics and a stable postoperative course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
(17 reference statements)
1
16
1
Order By: Relevance
“…In a trial by Leppikangas et al [40], 24 patients were randomised to receive a 24-hour infusion of either levosimendan or placebo prior to cardiac surgery; the authors found that levosimendan was associated with improved haemodynamic markers. Similar results were noted in patients undergoing coronary artery bypass grafting with left ventricular systolic dysfunction (left ventricular ejection fraction <30%) undergoing concomitant mitral valve repair, with advantages in a decreased need for ventilator support, and ICU and hospital length of stay [47].…”
Section: Pre-operative Administrationsupporting
confidence: 68%
“…In a trial by Leppikangas et al [40], 24 patients were randomised to receive a 24-hour infusion of either levosimendan or placebo prior to cardiac surgery; the authors found that levosimendan was associated with improved haemodynamic markers. Similar results were noted in patients undergoing coronary artery bypass grafting with left ventricular systolic dysfunction (left ventricular ejection fraction <30%) undergoing concomitant mitral valve repair, with advantages in a decreased need for ventilator support, and ICU and hospital length of stay [47].…”
Section: Pre-operative Administrationsupporting
confidence: 68%
“…After removal of duplicates, 423 findings were screened and 171 were excluded because they were not focused on the topic of interest. As shown in the PRISMA flow diagram in Additional file 2 , after the evaluation of the remaining 252 findings, only 6 RCTs were judged to be of interest for our quantitative analyses: 5 RCTs included only patients with preoperative severely depressed LVEF [ 13 , 19 22 ], and 1 RCT included both patients with preoperative severely depressed LVEF and patients with intra-/postoperative LCOS [ 14 ]. No study was focused only on patients with intra-/postoperative LCOS.…”
Section: Resultsmentioning
confidence: 99%
“…In six studies [ 13 , 14 , 19 22 ], both mortality and need for RRT were reported and were included in the primary outcome analysis. Mortality was similar overall (OR 0.64 [0.37, 1.11], p = 0.11, I 2 = 42%), but in the subgroup of patients with low LVEF, levosimendan showed a significantly lower mortality (OR 0.51 [0.32, 0.82], p = 0.005, I 2 = 0%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations